Amniotic membrane as a scaffold in wound healing and diabetic foot ulcer: an experimental technique and recommendations - Kannaiyan, Jaianand; S., SuriyaNarayanan; M., Palaniyandi; B., Rajangam; Chhabra, Hemlata; Pandey, Anubhav (International Journal of Research in Medical Sciences, 2017)
Background: Human amniotic membrane has been used clinically in a variety of applications for over the past 100 years and produced a significant amount of data in multiple areas of medicine. Its clinical usage ranges from wound coverage for burn victims to healing of the conjunctiva after pterygium repair. The amniotic membrane natural properties provide an easy to use, safe option for various medical applications. There is need to develop a method for storage of amniotic membrane which can retain the biological properties and as well have long shelf life too. Methods: The experimental technique was standardized for cryopreservation of amniotic membrane. For this, amniotic membrane was obtained from mothers who had delivered through caesarean section with their consent. Results: The standardized protocol for cryopreservation of amniotic membrane was found to be safe and preserved amniotic membrane is expected to have long shelf life. Conclusions: The advantages associated with amniotic membrane such as easily available, inexpensive, non-immunogenic and antimicrobial, anti-inflammatory properties make it a suitable graft to be used in wound healing and diabetic foot ulcers.